Money (Not) to Burn - Jack, B. Kelsey,Jayachandran, Seema,Kala, Namrata,Pande, Rohini (National Bureau of Economic Research, 2022)
Particulate matter significantly reduces life expectancy in India. We use a randomized controlled trial in the Indian state of Punjab to evaluate the effectiveness of conditional cash transfers (also known as payments for ecosystem services, or PES) in reducing crop residue burning, which is a major contributor to the region's poor air quality. Credit constraints and distrust may make farmers less likely to comply with standard PES contracts, which only pay the participant after verification of compliance. We randomize paying a portion of the money upfront and unconditionally. Despite receiving a lower reward for compliance, farmers offered partial upfront payment are 8-12 percentage points more likely to comply than are farmers offered the standard contract. Burning measures derived from satellite imagery indicate that PES with upfront payments significantly reduced burning, while standard PES payments were inframarginal. We also show that PES with an upfront component is a cost-effective way to improve India's air quality
Hardcopy version available to institutional subscribers
Keywords: Arbeitspapier; Graue Literatur; Getreideanbau; Luftverschmutzung; Agrarsubvention; Öffentliche Sozialleistungen; Feldforschung; Indien; Agriculture; Natural Resources; Energy; Environment; Other Primary Products; Sustainable Development; Environment and Development; Environment and Trade; Sustainability; Environmental Accounts and Accounting; Environmental Equity; Population Growth